Exploring the Viability and Efficacy of Fresh Slate Approach in India's Evolving Insolvency Framework - Singh, Vidhi; Sapre, Abhilash Arun; Shalini, Shalini; Shah, Shayeuq Ahmad (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
A nation's economy remains healthy and progressive because of the proper functioning of commercial and other business arrangements, transactions, and settlements. However, suppose such agreements are not concluded in the desired manner and result in failure. In that case, efforts are required to keep the corporation going with novel arrangements of liability and employment and re-negotiation between financiers. Nevertheless, the drowning company can resort to liquidation if survival becomes unworkable. The legislature and the judiciary have endeavoured to comply with and meet the objectives of the IBC. Adopting the new slate doctrine in the legal framework is one such step towards reaching the goal of the code. The code has facilitated the applicant's resolution by various means and balanced the corporate debtor's concern. The researcher has analytically analyzed this principle owing to its significance. In the initial phase, the research shed light on the doctrine of a fresh slate while referring to relevant legislative provisions and other jurisdictions. After that, the researcher explores the judicial wing's recognition and development of the doctrine. Principally, the researcher examines the status and management of disputed claims. In the latter segment, the researcher indicates the limitations and practical issues attached to the doctrine. Lastly, the researcher would make some suggestions that can be adopted and may aid in strengthening the Indian insolvency regime.